A Model of Effective Factors in Financial Restatements in Iran - Mohammad Reza Nikbakht (Shahid Bahonar University of Kerman, 2012)
Entities must restate their comparative financial statements when they correct prior periods accounting errors or change accounting methods. Although financial restatements have adverse effects on the relevance and reliability of financial statements’ information, financial restatement has increased considerably among listed companies in Tehran Stock Exchange, TSE, in the recent years. The main objective of this research is to identify the determinants of financial restatements in Iran. First, we recognized the effective factors by interviewing 50 experts, and then, using such factors, we estimated a logit regression model with observations on 202 listed companies in the TSE in the years 2004 to 2010. Our findings show that profitability, financial leverage, CEO duration, CEO change, auditors change, and audit firms size may affect financial restatements.